INTEGRASI BUDAYA LOKAL DALAM LAYANAN DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA SALATIGA DI ERA GLOKALISASI - Firda Nugraheni Cahyaningtyas; Muhammad Azhari Nur Alfian; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
Libraries as information centers have a strategic role in maintaining local cultural identity in the midst of globalization. Glocalization, a combination of global and local values, requires libraries to not only be adaptive to technological advances, but also uphold local wisdom. This article discusses how the Salatiga City Library and Archives Office (Dinpersip) can integrate local culture in library services in the era of glocalization. Through a descriptive qualitative approach. Data were collected through interviews, observations, and document studies. The role of the library in preserving local culture through the digitization of cultural collections, the implementation of literacy activities based on local traditions and the use of digital platforms that promote local content. The results of this study show that the integration of local culture in library services is able to strengthen the local cultural identity of the community, improve cultural literacy, and expand the reach of information services. The utilization of digital services such as ISalatiga, Perpuskita, Mocamoco, as well as innovations such as VR-based Virtual Tour, local book exhibitions, batik classes and cultural space arrangements make the library a reading space as well as an inspiring and adaptive cultural dialogue space in the era of glocalization. Thus, libraries are not only reading spaces, but also cultural dialog spaces that glue local values in a global culture.